Prognostic model integrating histology, systemic inflammation, and recurrence status predicts immunotherapy response in advanced non-small-cell lung cancer patients - F. V. Moiseenko; M. A. Krasavina; I. R. Agranov; E. V. Artemieva; A. P. Oganesian; A. S. Gabina; M. L. Makarkina; E. O. Elsakova; V. A. Henshtein; N. M. Volkov; V. V. Egorenkov; V. M. Moiseenko; et al. (Biology Direct)
Abstract Background Non-small-cell lung cancer (NSCLC) exhibits variable outcomes and remains a leading cause of cancer-related mortality, despite advances in immunotherapy. This study aimed to develop a prognostic model using real-world data (RWD) to stratify patients by survival outcomes and evaluate the benefit of immunotherapy across risk groups. Methods A retrospective cohort of 270 patients with NSCLC (2015–2024) treated with chemotherapy alone (54%) or chemoimmunotherapy (46%) was analyzed. Clinical, laboratory (neutrophil-to-lymphocyte ratio [NLR], platelet-to-lymphocyte ratio [PLR], monocyte-to-lymphocyte ratio [MLR]), and histopathological data were collected. Multivariate Cox regression identified prognostic factors for overall survival (OS) and validated them via bootstrapping. Results The cohort (median age, 65; 78% male) had a median OS of 11.2 months and a median progression-free survival (PFS) of 7.7 months. The final prognostic model incorporated histology (adenocarcinoma vs. large cell/squamous cell carcinoma/rare subtypes: HR = 1.6–2.03), recurrence state (HR = 0.51), and NLR (HR = 1.13). Patients were stratified into low- (median OS = 14.6 months) and high-risk (median OS = 9.6 months; p < 0.001) groups. Immunotherapy significantly increased PFS in low-risk patients (12.2 vs. 7.1 months, p = 0.002) and showed an increasing trend in OS (16.9 vs. 11.3 months, p = 0.12). High-risk patients derived no OS/PFS benefit (p ≥ 0.56). Conclusion This RWD-derived prognostic model effectively stratifies NSCLC patients into distinct risk groups. Immunotherapy-chemotherapy provided meaningful PFS improvement in low-risk patients but minimal benefit in high-risk subgroups, underscoring the need for tailored therapeutic strategies.